The Effect of Linezolid Therapy Duration on The Occurrence of Toxic Optic Neuropathy - Quinamora Estevan Sutantyo; Lukisiari Agustini; Tutik Kusmiati; Ariani Permatasari (AKSONA, 2026)
Highlight: The occurence of toxic optic neuropathy in this study was similar to the occurence of anemia. Discontinuation of Linezolid therapy improves visual disturbance Linezolid therapy duration to cause TON in this study varies   ABSTRACT Introduction: Linezolid is recommended by the World Health Organization (WHO) for the treatment of drug-resistant tuberculosis (DR-TB) because it improves treatment outcomes and therapy success. However, linezolid has several serious side effects, such as toxic optic neuropathy (TON). Previous studies have shown that various therapy durations are associated with the development of  TON, and the duration gap between linezolid exposure and TON occurrence remains inconclusive. Consequently, it is still unknown whether therapy duration affects the occurrence of TON. Objective: To identify the effect of linezolid therapy duration on the occurrence of TON among patients treated at the tuberculosis clinics of Dr. Soetomo General Academic Hospital, Surabaya, during the period from January 2020 to July 2021. Methods: This retrospective cohort study used data obtained from medical records, funduscopy examinations, Humphrey Field Analyser (HFA), and Optical Coherence Tomography (OCT). Results: A total of  30 subjects were included in this study, with a predominance of male patients (53.3% vs. 46.7%) and a mean age of 40.7 years. The most frequently administered dose of linezolid was 600 mg (n = 24), followed by 450 mg (n = 4), and 300 mg (n = 2). The majority of subjects (90%) received linezolid therapy for ≥6 months. TON occurred in 6 subjects, receiving 450 mg (n = 1) and 600 mg (n = 5). Visual symptoms improved following therapy termination.  The mean duration of linezolid to induce TON was 8.8 ± 1.5 months. Fisher’s exact test showed no significant association between linezolid therapy duration and TON (p-value = 1.000). Conclusion: Although all subjects who experienced TON had received linezolid therapy for ≥6 months, statistical analysis found no significant association between linezolid duration and the occurrence of TON.